2016
DOI: 10.1007/s13199-016-0406-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and menthol stress induce different cellular events during sea anemone bleaching

Abstract: International audienceCnidarian-dinoflagellate symbiosis disruption and subsequent bleaching are major concerns, especially regarding their ecological consequences on coral reefs and temperate coralligenous communities. Cnidarian bleaching is caused by a variety of environmental stressors, such as elevated seawater temperature associated with global climate change, and by pollutants, such as herbicides and metals. Several cellular events have been described to explain symbiosis dysfunction and bleaching. Exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 63 publications
0
27
1
Order By: Relevance
“…In the autophagic pathway, the target is enveloped in a membrane structure before lysosomal fusion, which initiates digestion by hydrolytic enzymes (Cuervo, 2004). Both apoptosis and autophagy have been observed during cnidarian bleaching and can occur simultaneously (Dunn et al, 2007) or alternatively in response to hyperthermal stress (Richier et al, 2006;Dani et al, 2016). In addition, another process related to symbiotic dinoflagellate autophagy has been reported in cnidarians and is referred to as "symbiophagy, " which results in the digestion of the resident dinoflagellates (Downs et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the autophagic pathway, the target is enveloped in a membrane structure before lysosomal fusion, which initiates digestion by hydrolytic enzymes (Cuervo, 2004). Both apoptosis and autophagy have been observed during cnidarian bleaching and can occur simultaneously (Dunn et al, 2007) or alternatively in response to hyperthermal stress (Richier et al, 2006;Dani et al, 2016). In addition, another process related to symbiotic dinoflagellate autophagy has been reported in cnidarians and is referred to as "symbiophagy, " which results in the digestion of the resident dinoflagellates (Downs et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we characterised both the abundance and localisation, at the cellular and subcellular levels, of NPC1, NPC2‐a, and NPC2‐d proteins in the cnidarian–dinoflagellate symbiosis. We applied both “normal” conditions and hyperthermal stress, to test the impacts of symbiosis dysfunction/“bleaching”; we also compared the impacts of menthol treatment, which causes host autophagy (Dani et al, ) and produces “healthy” aposymbiotic hosts (Matthews et al, ; Wang, Chen, Tew, Meng, & Chen, ). We demonstrated that NPC1 is localised both within vesicles in host tissues and to the perisymbiont membrane.…”
Section: Introductionmentioning
confidence: 99%
“…These include menthol (Wang, Chen, Tew, Meng, & Chen, 2012) and photosynthesis inhibitors (Jones, 2004) that result in bleaching. Several mechanisms have been identified that result in the degradation and expulsion of the symbionts, including apoptosis, necrosis, and symbiont digestion via autophagy (symbiophagy; Dani et al, 2016), and the mechanisms vary depending on the type of stress. Apoptosis and necrosis predominate in heat-stress bleaching, while symbiophagy predominates in menthol bleaching (Dani et al, 2016;Wang et al, 2012).…”
mentioning
confidence: 99%
“…Apoptosis and necrosis predominate in heat-stress bleaching, while symbiophagy predominates in menthol bleaching (Dani et al, 2016;Wang et al, 2012). Arrest of phagosomal maturation is required for the establishment of symbiosis, and Dani et al (2016) suggest that a re-engagement of phagosomal maturation is involved in the breakdown.…”
mentioning
confidence: 99%